Pandangan Hadis-Hadis Nabi Tentang Suluk dan Relevansinya dalam Pembentukan Karakter Muslim (Kajian Living Hadis Terhadap Tradisi di Masyarakat Besilam Tuan Guru Kecamatan Padang Tualang Kabupaten Langkat) - Abdul, Abdul Razak; Adnir, Farid (Ranah Research : Journal of Multidisciplinary Research and Development, 2025)
Suluk is practicing religion in its entirety in the aspects of faith, Islam and ihsan as well as developing character based on the Al-Quran and the Sunnah of the Prophet. Suluk involves the process of forming noble morals and self-transformation. However, the relevance of Jibril’s hadith which explains the three levels of faith to the practice of suluk among the younger generation of Muslims still needs further research. Researchers are interested in studying the practice of suluk in the Besilam Village community. This research is qualitative research using primary and secondary data sources. The results of this research show that Jibril’s hadith is an authentic hadith, and the relationship between Jibril’s hadith and the practice of suluk in Besilam Village are mutually relevant and play a role in shaping Muslim character. The practice of suluk goes through the stages of sharia, tariqah, to haqiqah in harmony with the level of faith in the hadith. Based on research conducted by the community, it is stated that sulik has been proven to change attitudes to be more obedient, have noble character, and be beneficial for the environment. This is in line with the goal of forming a complete Muslim person. It can be concluded that the hadith about suluk is relevant in shaping the character of the people of Besilam Village.